Clinical and radiologic comparison of dynamic cervical implant arthroplasty and cervical total disc replacement for single-level cervical degenerative disc disease. (May 2016) - Shichang, Liu; Yueming, Song; Limin, Liu; Lei, Wang; Zhongjie, Zhou; Chunguang, Zhou; Xi, Yang
Highlights: There are few studies on the incidence of adjacent segment disease (ASD) and heterotopic ossification (HO) in dynamic cervical implant (DCI) surgery. The rate of HO was 22.4% and 28.2% in the DCI and total disc replacement (TDR) groups, respectively. The rate of ASD and HO was not significantly different between the DCI and TDR groups. The cost of hospitalization was much higher in the TDR compared to the DCI group. Abstract: Anterior cervical discectomy and fusion, to date the most successful spine procedure for the surgical treatment of cervical radiculopathy, has limitations that have led to the development of non-fusion cervical procedures, such as cervical total disc replacement (TDR) and dynamic cervical implant (DCI) arthroplasty. We compared the clinical and radiological results of DCI and cervical TDR for the treatment of single-level cervical degenerative disc disease in Chinese patients. A retrospective review of 179 patients with cervical spondylotic myelopathy who underwent DCI or TDR between April 2010 and October 2012 was conducted, and 152 consecutive patients (67 patients single-level DCI and 85 single-level TDR) who completed at least 2 years of follow-up were included. Clinical and radiological assessments were performed preoperatively and at 1 week and 3, 6, 12, and 24 months postoperatively. The most common operative level was C5/C6 (49.3%). The differences in blood loss, duration of surgery, and duration of hospitalization were not statistically significant. The Japanese Orthopaedic Association scale, Visual Analog Scale, Neck Disability Index, and Short Form-36 scores improved significantly after surgery in both the DCI and TDR groups ( P   <  0.05), but the differences were not statistically significant at the final follow-up. The rate of occurrence of heterotopic ossification was 22.4% and 28.2% in the DCI and TDR groups, respectively. As an effective non-fusion technique, DCI is a more economical procedure. Further prospective, randomized studies with long-term follow-up periods are needed to determine the long-term effects.